Analysis Of The Implementation Of The Curriculum Based On The Qur'an And Hadith In Building Spiritual Character And Child-Friendly Boarding School At The MTS Baiturrahman NW Pemepek Boarding School - M. Khaerul Madjid H (International Journal of Technology and Education Research, 2026)
This study aims to analyze the implementation of the curriculum based on the Qur'an and Hadith in building spiritual character while integrating the concept of child-friendly Islamic boarding school at the Mts Baiturrahman NW Pemepek Islamic Boarding School, Central Lombok . The background of this research departs from the need for Islamic boarding schools to not only produce graduates who are fluent in religious knowledge, but also have a strong religious character and are able to adapt to the demands of modernization. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. Data analysis was carried out using the Miles & Huberman model which includes data reduction, data presentation, as well as drawing conclusions and verification interactively and continuously. This study confirms that the Qur'an-Hadith curriculum plays a significant role in shaping the spiritual character of students while supporting the concept of child-friendly Islamic boarding schools. To achieve optimal results, strengthening curriculum documentation, increasing teacher capacity, and improving infrastructure are necessary. This study provides an academic contribution in the form of an in-depth empirical study, as well as practical recommendations for developing a more holistic, contextual, and sustainable Islamic boarding school curriculum in Indonesia .